High-stability colorful heat insulation window film and preparation method thereof

By introducing a combination of nano-titanium dioxide, modified waterborne polyurethane emulsion, and graphene oxide into the window film, a multi-layer structure is formed, which solves the problems of poor hardness and UV resistance of traditional window films and achieves improved stability and heat insulation performance.

CN121005941AActive Publication Date: 2025-11-25NALINKO NEW MATERIALS (NANTONG) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511547177.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-28
Publication Date
2025-11-25
Estimated Expiration
2045-10-28

AI Technical Summary

Technical Problem

Traditional heat-insulating window films have poor UV protection, low hardness, and poor wear resistance, making them difficult to apply widely.

Method used

A UV absorption layer is formed by spraying nano-titanium dioxide dispersion, a hardened protective layer is formed by coating with modified waterborne polyurethane emulsion and graphene oxide polyurethane coating, and a color pattern layer is formed by printing iridescent dyes. The interlayer bonding is improved by multiple UV irradiation treatments.

Benefits of technology

It improves the hardness, abrasion resistance, and rigidity of the window film, while maintaining good impact resistance and UV protection, and enhances its heat insulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-stability colorful heat insulation window film and a preparation method thereof, and relates to the technical field of composite window films. A preparation method of the high-stability colorful heat insulation window film comprises the following steps: S1, cleaning and drying the surface of the base material layer, spraying a nano titanium dioxide dispersion liquid, and drying to form the UV absorption layer, so as to obtain a heat insulation window film A; s2, the surface of the UV absorption layer of the heat insulation window film A is coated with a polyurethane coating and cured, a hardened protection layer is formed, and a heat insulation window film B is obtained; and S3, printing a colorful dye on the surface of the hardened protection layer of the heat insulation window film B to form a colorful pattern layer so as to obtain the high-stability colorful heat insulation window film. The high-stability colorful heat insulation window film has excellent wear resistance and hardness, and keeps good impact resistance and anti-ultraviolet effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite window film technology, specifically a highly stable, colorful, heat-insulating window film and its preparation method. Background Technology

[0002] With the continuous advancement of technology, window films are being used more and more widely, especially in the fields of construction and automobiles. Heat-insulating window films not only provide a certain degree of protection, but also enhance aesthetics and safety, and provide functions such as heat insulation and UV protection. However, traditional heat-insulating window film products generally have poor UV protection, with a UV blocking rate usually below 90%. Moreover, ordinary window films are relatively soft, have low hardness, and poor wear resistance, making them difficult to apply widely.

[0003] In conclusion, solving the above problems and preparing a highly stable, colorful, heat-insulating window film is of great significance. Summary of the Invention

[0004] The purpose of this invention is to provide a highly stable, colorful, heat-insulating window film and its preparation method, so as to solve the problems mentioned in the background art.

[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a highly stable, colorful, heat-insulating window film includes the following steps: S1: After cleaning and drying the surface of the substrate layer, spray nano titanium dioxide dispersion, dry it to form a UV absorption layer, and obtain heat insulation window film A; S2: Coat the UV absorption layer surface of the heat insulation window film A with polyurethane coating and cure it to form a hardened protective layer, thus obtaining the heat insulation window film B; S3: Print iridescent dyes on the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0006] Preferably, the polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.1~0.3; wherein the graphene oxide has a sheet diameter of 0.5~3μm.

[0007] Preferred method for preparing the modified waterborne polyurethane emulsion includes the following steps: (1) Under a nitrogen atmosphere, polyether polyol and 2,2-dimethylolpropionic acid are added to a reaction vessel, acetone is added, and the mixture is stirred at 40-45°C until completely dissolved. Isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred at 75-80°C for 20-30 min. An anti-UV chain extender is added, and the mixture is stirred at 80-85°C for 1-2 h. Hydroxyethyl methacrylate is added, and the mixture is stirred for 40-60 min. Acetone is removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, waterborne polyurethane and methyl methacrylate are added to acetone and stirred evenly. Deionized water is added and stirred to form an emulsion. Triethylamine is added to adjust the pH to 7. 1~1.5wt% ammonium persulfate is added and the mixture is refluxed and stirred at 80~85℃ for 2~3h. Acetone is removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion.

[0008] Preferably, the waterborne polyurethane comprises the following raw materials, by weight: 40-45 parts polyether polyol, 6-7 parts 2,2-dimethylolpropionic acid, 25 parts acetone, 15-17 parts isophorone diisocyanate, 0.01-0.02 parts dibutyltin dilaurate, 2-3 parts UV-resistant chain extender, and 3-4 parts hydroxyethyl methacrylate; The modified waterborne polyurethane emulsion comprises the following raw materials, by weight: 38-40 parts waterborne polyurethane, 8-10 parts methyl methacrylate, 25 parts acetone, and 30-40 parts deionized water.

[0009] Preferred method for preparing the UV-resistant chain extender includes the following steps: adding 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stirring until homogeneous; adding the UV-resistant agent; stirring rapidly at 80-85°C for 35-45 minutes; adjusting the pH to 6; filtering to obtain the filtrate; removing the solvent by rotary evaporation; and drying to obtain the UV-resistant chain extender. The molar ratio of 4,4',4''-methylenetriphenol to the UV absorber is 1:1 to 1.1; the UV absorber is a reactive anionic UV absorber based on the oxaloylaniline group.

[0010] Preferably, the nano-titanium dioxide dispersion comprises the following raw materials, in 100 parts by weight: 8-12 parts modified titanium dioxide, 1-1.5 parts methyl methacrylate, 0.5-0.8 parts aqueous polyurethane, 0.01-0.02 parts ammonium persulfate, and the remainder being deionized water; The spraying amount of the nano-titanium dioxide dispersion is 40~60 g / m². 2 ; The substrate layer includes either PET film or PVC plastic sheet, with a thickness of 50~200μm.

[0011] Preferred method for preparing modified nano-titanium dioxide includes the following steps: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 60-70 wt% ethanol solution and ultrasonically disperse them evenly. Stir at 50-60℃ for 3-5 h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water and stirred evenly. 0.4~0.6wt% of azobisisobutyronitrile was added and stirred at 60~70℃ for 2~3h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide. The mass ratio of nano-titanium dioxide to 3-mercaptopropyltriethoxysilane is 1:0.2~0.4. The mass ratio of polyethylene glycol divinyl ether to mercapto-modified nano-titanium dioxide is 0.6~0.8:1.

[0012] Preferably, in step S2, the preparation method of the heat insulation window film B specifically includes the following steps: coating the surface of the UV absorption layer in the heat insulation window film A with polyurethane coating, performing a first ultraviolet light treatment, coating the polyurethane coating again, performing a second ultraviolet light treatment, drying, forming a hardened protective layer, and obtaining the heat insulation window film B.

[0013] Preferably, the duration of the first ultraviolet irradiation treatment is 5-10 min, and the duration of the second ultraviolet irradiation treatment is 20-25 min; the coating thickness of the polyurethane coating is 15-20 μm.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the high-stability colorful heat insulation window film of the present invention is composed of a substrate layer, a UV absorption layer, a hardening protective layer, and a color pattern layer; the prepared window film has excellent wear resistance and hardness, and maintains good impact resistance and UV protection.

[0015] The substrate layer preferably uses PET film as the base material, which ensures flexibility and mechanical strength while also having good light transmittance. The UV absorption layer is obtained by spraying and curing nano-titanium dioxide dispersion. The hardened protective layer is formed by curing polyurethane coating obtained by mixing modified waterborne polyurethane emulsion and graphene oxide. The color pattern layer can be customized with color patterns according to requirements. The use of iridescent dyes can effectively block solar heat and provide excellent heat insulation performance.

[0016] The modified waterborne polyurethane emulsion is prepared by reacting polyether polyol and isophorone diisocyanate, using 2,2-dimethylolpropionic acid as a waterborne chain extender and adding an anti-UV chain extender, and using hydroxyethyl methacrylate as a capping agent to prepare waterborne polyurethane, and then adding methyl methacrylate for copolymerization to obtain the modified waterborne polyurethane emulsion; the anti-UV chain extender is prepared by reacting the oxygen anion formed after the dissociation of one phenolic hydroxyl group of 4,4',4''-methylenetriphenol with the vinyl sulfone group formed by the hydrolysis of the reactive anionic UV absorber of oxaloylaniline group.

[0017] Among them, the modified waterborne polyurethane emulsion prepared by copolymerizing alkenyl-terminated waterborne polyurethane and methyl methacrylate can greatly improve the hardness and wear resistance of the hard protective layer and enhance the protection against hard particles. The addition of the anti-UV chain extender, on the one hand, endows the hardened protective layer with a certain UV absorption, which synergistically improves the anti-UV effect with the UV absorption layer. On the other hand, the anionic groups contained in the anti-UV chain extender further improve the emulsification performance of the waterborne polyurethane, thereby improving the film-forming properties of the modified waterborne polyurethane emulsion and improving the hardness and wear resistance of the hardened protective layer.

[0018] In this invention, the titanium dioxide in the nano-titanium dioxide dispersion is promoted by the aqueous polyurethane and methyl acrylate prepared in the previous step, which improves the UV protection effect. Its cured structure and hardened protective layer have certain similarities, and it provides excellent interlayer bonding force in subsequent curing to prevent coating peeling. Furthermore, this invention introduces mercapto groups on the surface of nano-titanium dioxide using 3-mercaptopropyltriethoxysilane and then clicks it with polyethylene glycol divinyl ether, thereby improving the dispersibility of nano-titanium dioxide. At the same time, the polyethylene glycol structure gives the UV absorption layer good toughness, thereby improving the overall impact resistance of the window film.

[0019] The polyurethane coating is obtained by mixing modified waterborne polyurethane emulsion and graphene oxide, and forms a hardened protective layer after being coated and cured by ultraviolet light. Graphene oxide possesses high thermal conductivity and reflectivity, effectively reflecting and blocking infrared rays to improve the heat insulation performance of window films. It also helps enhance the hardness and wear resistance of the coating. Through ultraviolet (UV) irradiation, the water in the coating, after being excited by UV light, generates hydrated electrons that reduce the oxygen-containing groups on the surface of graphene oxide, increasing its rigidity. This also promotes the reaction between the oxygen-containing groups of graphene oxide and the groups in the waterborne polyurethane in the coating, increasing the density of the coating and thus improving the hardness of the hardened protective layer. However, the inventors found that the treated coating is relatively brittle and prone to cracking after impact, reducing its heat insulation and UV protection effects. This may be due to the large coating thickness, limited UV penetration depth, significant difference in the reduction rate of graphene between the surface and bottom layers, and high internal stress. Therefore, this invention employs a double coating and UV irradiation treatment, with the single UV treatment time being less than the double treatment time. This helps improve the impact resistance of the window film without affecting surface hardness. Furthermore, this design facilitates a tighter bond between the hardened protective layer and the UV-resistant layer, reducing the risk of detachment and improving stability. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] It should be noted that the following quantities are by weight. There are no special restrictions on the suppliers of any of the raw materials involved in this invention. Exemplary examples include: nano-titanium dioxide with a particle size of 50-100 nm; CAS number 14814-09-6 for 3-mercaptopropyltriethoxysilane; polyethylene glycol divinyl ether with a molecular weight of 1000; CAS number 603-44-1 for 4,4',4''-methylenetriphenol; and UV absorber: a reactive UV absorber based on N,N'-diphenylethylenediamide, model UV-SCL, manufactured by Suzhou Yatu Textile Auxiliaries Co., Ltd. The company provides: polytetrahydrofuran diol with a molecular weight of 1000; 2,2-dimethylolpropionic acid (CAS number: 4767-03-7); isophorone diisocyanate (CAS number: 4098-71-9); dibutyltin laurylate (CAS number: 77-58-7); hydroxyethyl methacrylate (CAS number: 868-77-9); methyl methacrylate (CAS number: 80-62-6); triethylamine (CAS number: 121-44-8); polyvinylpyrrolidone (CAS number: 9003-39-8); and graphene oxide with a sheet diameter of 0.5~3μm.

[0022] In the following embodiments, parts refer to parts by weight, and all raw materials mentioned above and others not mentioned are commercially available; the substrate layer is a PET film with a thickness of 100 μm.

[0023] Example 1: The preparation method of high-stability, colorful heat-insulating window film includes the following steps: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0024] Step 2: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 3: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 4: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 50 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 10 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 20 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0025] Example 2: The preparation method of high-stability colorful heat-insulating window film includes the following steps: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0026] Step 2: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 3: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 4: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 40 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 5 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 25 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0027] Example 3: The preparation method of high-stability colorful heat-insulating window film includes the following steps: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0028] Step 2: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 3: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 4: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 60 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 5 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 25 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0029] Comparative Example 1: Based on Example 1, without introducing an anti-UV chain extender, the remaining processes remain unchanged, as follows: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0030] Step 2: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 9 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min and at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 3: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 50 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 10 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 20 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0031] Comparative Example 2: Based on Example 1, the nano-titanium dioxide was not modified, and the remaining processes remained unchanged, as follows: Step 1: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 2: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 3: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 50 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts nano-titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 10 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 20 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0032] Comparative Example 3: Based on Example 1, only one ultraviolet treatment was performed, with the remaining processes unchanged, as follows: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0033] Step 2: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 3: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 4: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 50 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: Coat the surface of the UV absorption layer in the heat insulation window film A with a polyurethane coating of 40 μm thickness, and treat it with ultraviolet light for 30 min to obtain the heat insulation window film B; wherein, the polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0034] Comparative Example 4: Based on Example 1, the UV treatment time was the same for both trials, and the remaining processes remained unchanged, as follows: Step 1: Preparation of modified nano-titanium dioxide: (1) Add nano-titanium dioxide and 3-mercaptopropyltriethoxysilane to a 70wt% ethanol solution at a mass ratio of 1:0.3 and disperse evenly by ultrasonication. Stir at 55℃ for 4h, filter, wash, and dry to obtain mercapto-modified nano-titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water at a mass ratio of 0.9:1 and stirred until homogeneous. 0.5 wt% of azobisisobutyronitrile was added and stirred at 70°C for 2.5 h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide.

[0035] Step 2: Preparation of UV-resistant chain extender: Add 4,4',4''-methylenetriphenol to a sodium carbonate solution with pH 9 and stir until homogeneous. Add a UV-resistant agent with a molar ratio of 1:1.1, stir rapidly at 80℃ for 40 min, adjust the pH to 6, filter to obtain the filtrate, remove the solvent by rotary evaporation, and dry to obtain the UV-resistant chain extender. Step 3: Preparation of modified waterborne polyurethane emulsion: (1) Under a nitrogen atmosphere, 42 parts of polytetrahydrofuran diol and 6.5 parts of 2,2-dimethylolpropionic acid were added to the reactor, 25 parts of acetone were added, and the mixture was stirred at 45°C until completely dissolved. 16 parts of isophorone diisocyanate and 0.01 parts of dibutyltin dilaurate were added, and the mixture was stirred at 80°C for 25 min. 2.5 parts of UV-resistant chain extender were added, and the mixture was stirred at 85°C for 1.5 h. 3.5 parts of hydroxyethyl methacrylate were added, and the mixture was stirred for another 50 min. The acetone was removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, 40 parts of waterborne polyurethane and 10 parts of methyl methacrylate were added to 25 parts of acetone and stirred evenly. 35 parts of deionized water were added and stirred to form an emulsion. Triethylamine was added to adjust the pH to 7. 1.5 wt% of ammonium persulfate was added and the mixture was refluxed and stirred at 85 °C for 2.5 h. The acetone was removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion. Step 4: Preparation of high-stability, vibrant color-insulating window film: S1: After cleaning and drying the substrate surface, spray a nano-titanium dioxide dispersion at a rate of 50 g / m². 2 The mixture is dried to form a UV absorption layer, resulting in a heat-insulating window film A. The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 10 parts modified titanium dioxide, 1.2 parts methyl methacrylate, 0.6 parts aqueous polyurethane, 0.01 parts ammonium persulfate, and the remainder being deionized water. S2: A polyurethane coating with a thickness of 20 μm is applied to the surface of the UV absorption layer in the heat insulation window film A. It is then subjected to a first UV irradiation treatment for 15 min, followed by a second application of the polyurethane coating with a thickness of 20 μm, and a second UV irradiation treatment for 15 min. After drying, a hardened protective layer is formed, resulting in the heat insulation window film B. The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.2. S3: Screen print iridescent dyes onto the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

[0036] Performance test (1): Heat insulation window film B was prepared according to the scheme of Example 1 and Comparative Example 1 to form samples, and the following tests were performed respectively: abrasion resistance was measured according to GB / T 1768-2006; pencil hardness was measured according to GB / T 6739-2006; ultraviolet transmittance was measured according to GB / T2680-2021; and impact resistance was measured according to GB / T 1732-2020. The experimental data are shown in Table 1.

[0037] Table 1

[0038] As shown in Table 1, the window film prepared by this invention has excellent wear resistance and hardness, while maintaining good impact resistance and UV protection. In Comparative Example 1, no UV-resistant chain extender was introduced, resulting in increased UV transmittance. Therefore, the UV absorption layer and the hardened protective layer with added UV-resistant chain extender have a good synergistic effect. At the same time, the anionic groups contained in the UV-resistant chain extender further promote the emulsification of waterborne polyurethane. Therefore, compared with the simple waterborne chain extender, the wear resistance of the coating is improved, resulting in a good protective effect.

[0039] Performance test (2): Heat insulation window film B was prepared according to the schemes of Examples 1-3 and Comparative Examples 1-4, and samples were formed. The following tests were performed respectively: abrasion resistance was measured according to GB / T 1768-2006; impact resistance was measured according to GB / T 1732-2020. The experimental data are shown in Table 2.

[0040] Table 2

[0041] As shown in Table 2, in Comparative Example 2, the nano-titanium dioxide was not modified, resulting in decreased dispersibility and reduced toughness of the UV absorption layer, thus reducing impact resistance. In Comparative Example 3, only one UV treatment was performed, resulting in a thicker coating, limited UV penetration depth, and a large difference in the reduction rate of graphene between the surface and bottom layers, leading to high internal stress and reduced impact resistance. In Comparative Example 4, the two UV treatments were performed for the same time. Due to the relatively short second treatment time, the surface graphene was not completely reduced, resulting in decreased hardness and reduced wear resistance. However, compared with Comparative Example 3, the impact strength was significantly improved.

[0042] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a highly stable, colorful, heat-insulating window film, characterized in that: Includes the following steps: S1: After cleaning and drying the surface of the substrate layer, spray nano titanium dioxide dispersion, dry it to form a UV absorption layer, and obtain heat insulation window film A; S2: Coat the UV absorption layer surface of the heat insulation window film A with polyurethane coating and cure it to form a hardened protective layer, thus obtaining the heat insulation window film B; S3: Print iridescent dyes on the surface of the hardened protective layer of the heat-insulating window film B to form a color pattern layer, resulting in a highly stable iridescent heat-insulating window film.

2. The method for preparing a high-stability, vibrant color-insulating window film according to claim 1, characterized in that: The polyurethane coating comprises a modified waterborne polyurethane emulsion and graphene oxide in a mass ratio of 100:0.1~0.3; wherein the graphene oxide has a sheet diameter of 0.5~3μm.

3. The method for preparing a high-stability, colorful, heat-insulating window film according to claim 2, characterized in that: The preparation method of the modified waterborne polyurethane emulsion includes the following steps: (1) Under a nitrogen atmosphere, polyether polyol and 2,2-dimethylolpropionic acid are added to a reaction vessel, acetone is added, and the mixture is stirred at 40~45℃ until completely dissolved. Isophorone diisocyanate and dibutyltin dilaurate are added, and the mixture is stirred at 75~80℃ for 20~30 min. An anti-ultraviolet chain extender is added, and the mixture is stirred at 80~85℃ for 1~2 h. Hydroxyethyl methacrylate is added, and the mixture is stirred for 40~60 min. Acetone is removed by rotary evaporation to obtain waterborne polyurethane. (2) Under a nitrogen atmosphere, waterborne polyurethane and methyl methacrylate are added to acetone and stirred evenly. Deionized water is added and stirred to form an emulsion. Triethylamine is added to adjust the pH to 7. 1~1.5wt% ammonium persulfate is added and the mixture is refluxed and stirred at 80~85℃ for 2~3h. Acetone is removed by rotary evaporation to obtain the modified waterborne polyurethane emulsion.

4. The method for preparing a high-stability, colorful, heat-insulating window film according to claim 3, characterized in that: The waterborne polyurethane comprises the following raw materials, by weight: 40-45 parts polyether polyol, 6-7 parts 2,2-dimethylolpropionic acid, 25 parts acetone, 15-17 parts isophorone diisocyanate, 0.01-0.02 parts dibutyltin dilaurate, 2-3 parts UV-resistant chain extender, and 3-4 parts hydroxyethyl methacrylate; The modified waterborne polyurethane emulsion comprises the following raw materials, by weight: 38-40 parts waterborne polyurethane, 8-10 parts methyl methacrylate, 25 parts acetone, and 30-40 parts deionized water.

5. The method for preparing a high-stability, colorful, heat-insulating window film according to claim 3, characterized in that: The preparation method of the UV-resistant chain extender includes the following steps: 4,4',4''-methylenetriphenol is added to a sodium carbonate solution with pH 9 and stirred evenly; a UV-resistant agent is added; the mixture is stirred rapidly at 80-85℃ for 35-45 minutes; the pH is adjusted to 6; the filtrate is filtered; the solvent is removed by rotary evaporation; and the mixture is dried to obtain the UV-resistant chain extender. The molar ratio of 4,4',4''-methylenetriphenol to the UV absorber is 1:1 to 1.1; the UV absorber is a reactive anionic UV absorber based on the oxaloylaniline group.

6. The method for preparing a high-stability, vibrant color-insulating window film according to claim 1, characterized in that: The nano-titanium dioxide dispersion comprises the following raw materials, in parts by weight: 8-12 parts modified titanium dioxide, 1-1.5 parts methyl methacrylate, 0.5-0.8 parts aqueous polyurethane, 0.01-0.02 parts ammonium persulfate, and the remainder is deionized water; The spraying amount of the nano-titanium dioxide dispersion is 40~60 g / m². 2 ; The substrate layer includes either PET film or PVC plastic sheet, with a thickness of 50~200μm.

7. The method for preparing a high-stability, colorful, heat-insulating window film according to claim 6, characterized in that: The preparation method of the modified nano titanium dioxide includes the following steps: Step 1: Preparation of modified nano titanium dioxide: (1) Add nano titanium dioxide and 3-mercaptopropyltriethoxysilane to a 60~70wt% ethanol solution and ultrasonically disperse them evenly. Stir at 50~60℃ for 3~5h, filter, wash, and dry to obtain mercapto-modified nano titanium dioxide. (2) Polyethylene glycol divinyl ether and mercapto-modified nano-titanium dioxide were added to deionized water and stirred evenly. 0.4~0.6wt% of azobisisobutyronitrile was added and stirred at 60~70℃ for 2~3h. The mixture was then filtered, washed, and dried to obtain modified nano-titanium dioxide. The mass ratio of nano-titanium dioxide to 3-mercaptopropyltriethoxysilane is 1:0.2~0.

4. The mass ratio of polyethylene glycol divinyl ether to mercapto-modified nano-titanium dioxide is 0.6~0.8:

1.

8. The method for preparing a high-stability, vibrant color-insulating window film according to claim 1, characterized in that: In step S2, the preparation method of the heat insulation window film B specifically includes the following steps: coating the surface of the UV absorption layer in the heat insulation window film A with polyurethane coating, performing a first ultraviolet light treatment, coating the polyurethane coating again, performing a second ultraviolet light treatment, drying, forming a hardened protective layer, and obtaining the heat insulation window film B.

9. The method for preparing a high-stability, colorful, heat-insulating window film according to claim 8, characterized in that: The duration of the first ultraviolet irradiation treatment is 5-10 minutes, and the duration of the second ultraviolet irradiation treatment is 20-25 minutes; the coating thickness of the polyurethane coating is 15-20 μm.

10. A high-stability, colorful, heat-insulating window film prepared by the method of preparing a high-stability, colorful, heat-insulating window film according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Corrosion-resistant polyester powder coating and preparation method thereof

    CN116948508A

  • Wear-resistant high-strength glass protection safety film and preparation method thereof

    CN119639051A

  • Highly wear-resistant water-based elastomeric coating for surface decoration of plastic materials

    WO2022048065A1